Factors influencing trends in opioid prescribing for older people: a scoping review. (24th September 2020) - Mikelyte, Rasa; Abrahamson, Vanessa; Hill, Emma; Wilson, Patricia M.
Abstract: Aim: The review aimed to identify factors influencing opioid prescribing as regular pain-management medication for older people. Background: Chronic pain occurs in 45%–85% of older people, but appears to be under-recognised and under-treated. However, strong opiate prescribing is more prevalent in older people, increasing at the fastest rate in this age group. Methods: This review included all study types, published 1990–2017, which focused on opioid prescribing for pain management among older adults. Arksey and O'Malley's framework was used to scope the literature. PubMed, EBSCO Host, the UK Drug Database, and Google Scholar were searched. Data extraction, carried out by two researchers, included factors explaining opioid prescribing patterns and prescribing trends. Findings: A total of 613 papers were identified and 53 were included in the final review consisting of 35 research papers, 10 opinion pieces and 8 grey literature sources. Factors associated with prescribing patterns were categorised according to whether they were patient-related, prescriber-driven, or system-driven. Patient factors included age, gender, race, and cognition; prescriber factors included attitudes towards opioids and judgements about 'normal' pain; and policy/system factors related to the changing policy landscape over the last three decades, particularly in the USA. Conclusions: A large number of context-dependent factors appeared to influence opioid prescribing for chronic pain management in older adults, but the findings were inconsistent. There is a gap in the literature relating to the UK healthcare system; the prescriber and the patient perspective; and within the context of multi-morbidity and treatment burden.